2001
DOI: 10.1091/mbc.12.9.2846
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Autoregulation and Inhibition of mRNA Translation of Amino Acid Regulator GenecpcAof Filamentous FungusAspergillus nidulans

Abstract: The CPCA protein of the filamentous fungus Aspergillus nidulans is a member of the c-Jun-like transcriptional activator family. It acts as central transcription factor of the cross-pathway regulatory network of amino acid biosynthesis and is functionally exchangeable for the general control transcriptional activator Gcn4p of Saccharomyces cerevisiae. In contrast to GCN4, expression of cpcA is strongly regulated by two equally important mechanisms with additive effects that lead to a fivefold increased CPCA pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 64 publications
3
86
0
1
Order By: Relevance
“…Many of these genes are well-known target genes of a complex transcriptional system, referred to as the CPC network, which enables yeast cells and filamentous fungi to respond to amino acid starvation (28,43,50). In general, starvation for a single amino acid results in specific uncharged tRNAs activating the sensor kinase Cpc3 followed by activation of the central transcriptional activator Cpc1, which induces genes involved in the biosynthesis of amino acids, purines, or aminoacyl-tRNA synthetases among others (reviewed in reference 33).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these genes are well-known target genes of a complex transcriptional system, referred to as the CPC network, which enables yeast cells and filamentous fungi to respond to amino acid starvation (28,43,50). In general, starvation for a single amino acid results in specific uncharged tRNAs activating the sensor kinase Cpc3 followed by activation of the central transcriptional activator Cpc1, which induces genes involved in the biosynthesis of amino acids, purines, or aminoacyl-tRNA synthetases among others (reviewed in reference 33).…”
Section: Discussionmentioning
confidence: 99%
“…1), were considered to be translated into the IE1 protein at this novel, intermediate stage. For some mRNAs that have small uORFs that restrict the translation of the downstream ORFs, it has been reported that modulation of both translational regulation and the mRNA level is important for release from the uORF control (14,28). An alteration in the regulation of translation as well as the increase of the H6LTs might have contributed to the increased IE1 protein expression (Table 2).…”
Section: Vol 77 2003mentioning
confidence: 99%
“…In addition to the feedback control of yeast Aro3p and Aro4p, the transcription of the corresponding genes is part of a complex regulatory network that couples transcriptional derepression of Ͼ500 genes to the availability of amino acids (22). This regulatory network is conserved between several fungi and is known as ''cross-pathway control'' in molds or as ''general control'' of amino acid biosynthesis in yeast (23)(24)(25). A key factor is the transcriptional activator Gcn4p of yeast and its interchangeable counterparts including, e.g., CPCA of A. nidulans (24).…”
mentioning
confidence: 99%
“…This regulatory network is conserved between several fungi and is known as ''cross-pathway control'' in molds or as ''general control'' of amino acid biosynthesis in yeast (23)(24)(25). A key factor is the transcriptional activator Gcn4p of yeast and its interchangeable counterparts including, e.g., CPCA of A. nidulans (24). Gcn4p binds to the promoter region of target genes to a well characterized upstream activation site.…”
mentioning
confidence: 99%